Environmental education and the ecological-taxonomic study of marine invertebrates associated with rhodoliths/maërl beds in tropical coast - Costa, Dimítri de Araújo (2020)
This thesis aimed to provide students from public elementary schools in the Northeast Brazil with a differentiated and innovative way of teaching, using Environmental Education to raise their awareness for the protection of local coastal marine environments. The rhodolith/maërl beds are among the local potential environments to use for that purpose, since they are highly abundant on the Brazilian northeast coast, but still poorly known in the region. As such, the thesis also aimed to contribute to improve the knowledge of this habitat, with respect to local abundance, associated invertebrate communities, ecological importance and the impact of environmental constraints. The study was conducted in two schools in João Pessoa and Mataraca municipalities, in the State of Paraíba, integrating non-formal education, through a sequential program of practical activities, with traditional formal education. The efficiency of the program was tested with a questionnaire. In general, the integrated teaching was effective, since at the end of the program more than 80% of the students responded according to the concepts taught, demonstrating an improved level of ocean literacy. Regarding the rhodolith beds, a literature review was carried out, that confirmed their worldwide distribution and ecological importance, including for the balance of coastal ecosystems and maintenance of marine life. As a further research, the first taxonomic study of the invertebrates associated with rhodoliths was carried out on the beaches of Miramar (municipality of Cabedelo), Seixas (João Pessoa) and Maceió (Pitimbu). Sixty species were collected and identified, from different taxa. Of these, 53 were new records for the beaches under study, some of which may even be new species and/or endemic to rhodoliths. Finally, the rhodolith beds of these beaches, subjected to different anthropogenic impacts, were characterized, from the rhodoliths’ abundance, morphology, growth form, as well as the associated invertebrates, according to the environmental factors assessed at the study sites. In general, Seixas Beach presented the greatest abundance of rhodoliths, and diversity and abundance of associated invertebrates, a result related to the high levels of calcium carbonate in the region, since this is an essential component for the development of calcareous algae. Maceió beach had the lowest abundance of these organisms, mainly associated with the high level of contamination by thermotolerant coliforms and lower water transparency. The invertebrate communities were also analysed from a functional perspective. Miramar and Seixas beaches were similar, where biodiffusors, with free and slow movement and predators predominated; whereas in Maceió Beach these attributes were practically absent, with individuals with limited movement, limited sediment remobilization and suspended feeding. These differences were analysed according to habitat characteristics, whose rhodolith-invertebrate interaction may be more beneficial in Seixas and Miramar beaches.